2004
DOI: 10.1177/1049732304265959
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Representation within Qualitative Inquiry

Abstract: Although qualitative inquiry has developed into a popularized and very useful way of conducting research within the health sciences, there has been a relatively disproportionate amount of literature devoted to "who" is represented in such inquiries. It is most often assumed that the end text should present an objective, value-free, and accurate representation of the participants and therefore exclude by all means the researcher's presence from the study. Although this might hold grounds for some inquiries, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 38 publications
2
47
0
9
Order By: Relevance
“…Interpretive research also assumes that reality is socially constructed and that the researcher becomes the vehicle by which this reality is revealed (Walsham, 1995;Cavana et al, 2001). Hence, the researchers are not divorced from the phenomenon under study, but they must take into account their own position in the setting and situation as they are the main research tool (Mantzoukas, 2004). Being considered as a research tool is consistent with the construction of the social world characterised by interaction between the researcher and the participants (Mingers, 2001).…”
Section: Designmentioning
confidence: 99%
“…Interpretive research also assumes that reality is socially constructed and that the researcher becomes the vehicle by which this reality is revealed (Walsham, 1995;Cavana et al, 2001). Hence, the researchers are not divorced from the phenomenon under study, but they must take into account their own position in the setting and situation as they are the main research tool (Mantzoukas, 2004). Being considered as a research tool is consistent with the construction of the social world characterised by interaction between the researcher and the participants (Mingers, 2001).…”
Section: Designmentioning
confidence: 99%
“…Nonetheless, it has been suggested that the criterion of generalizability be replaced by transferability . In the qualitative literature, transferability of a research study implies the development of knowledge that, through critical reading and decision-making, can be contested and shared (Malterud, 2002;Mantzoukas, 2004). It places a requirement on researchers to give detailed descriptions of the intervention, context and process of data production to allow readers to assess the transferability to their settings Øvretveit, 2002).…”
Section: Why Complexity Theory Is Important For Economic Evaluation Imentioning
confidence: 99%
“…Medical and biomedical sciences are dominated by the logical positivism of traditional science which assumes the existence of an objective and universal reality, and considers researchers as independent observers (FitzGerald, 1995;Herman, 1992;Kneebone, 2002;Malterud, 2002). However, contemporary theory of knowledge realizes that all scientific knowledge (including laboratory facts) is constructed and reflects the researchers' standpoints, thus criticizing the belief of a neutral observation (Haggerty, 2003;Latour & Woolgar, 1986;Lynch, 2000;Malterud, 2002;Mantzoukas, 2004). All scientific facts must be conquered, constructed, and confirmed (Bourdieu, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could take us further into complicated ethical dilemmas of the various aspects of qualitative research. [4,5] Mencius, a Confucian thinker, said in <Gaozi> that "Fish are my favorite; bear's paws are also my favorites. If I cannot have both, I will choose bear's paws over fish."…”
Section: Introductionmentioning
confidence: 99%